Penggunaan Banten Dewa-Dewi pada Upacara Piodalan di DKI Jakarta (Tinjauan Bentuk, Fungsi dan Makna) - Nyoman Widasni; Anak Agung Oka Puspa; I Made Sutresna (Jurnal PASUPATI, 2020)
This thesis discusses "The Use of the Banten Dewa-dewi at the Piodalan Ceremony in DKI Jakarta (Overview of Form, Function and Meaning)". This study aims to obtain the form, function and meaning of the Banten of the Dewa-dewi so that the offer can be used as a means of carrying out the Piodalan ceremony. This research is a qualitative research with descriptive design, using unstructured interviews or in-depth interviews as data collection techniques and data management so that the authors do not make a list of standard or structural questions in data management in order to prevent things that intervene informants. The author conducted an interview with the informant who is a sulinggih, serati banten, and lecturer of Hindu religious events domiciled in DKI Jakarta. In addition, the authors use the literature method as secondary data to support the statements of the informants. The data that I get through the collection techniques above, the authors analyze and manage data so that it gets results the meaning of the banten of the Dewa-dewi as the place where Ida Sang Hyang Widhi went on when the Piodalan ceremony was held, because God's intangible capacity will be difficult to be worshiped by Hindus who are bound by worldliness. The Banten of Dewa-dewi also have meaning as symbols of God in the form of Ardhanareswari (Purusa and Pradhana as the beginning of the Creation of the universe so that they can provide balance in life.